Better Late Than Never - A Case of a Congenital Left Partial Anomalous Pulmonary Venous Drainage Diagnosed and Treated in The Sixth Decade of Life - Elbayomi, Mohamed; Pathare, Presheet; Nooh, Ehab; Harig, Frank; Abdullayev, Farid; Weyand, Michael (Heart Surgery Forum, 2023)
Partial anomalous pulmonary venous drainage (PAPVD) is a relatively uncommon cardiac anomaly. The diagnosis might be challenging as are the presenting symptoms. Its clinical course mimics more familiar diseases, e.g., pulmonary artery embolism. We present a case of PAPVD, which had been misdiagnosed for more than two decades. After establishing the correct diagnosis, the patient got his congenital anomaly surgically corrected and showed excellent cardiac recovery in the six months follow up.
CRIS-Team Scopus Importer:2023-04-07